Poranek dyskusyjny na temat Nowoczesna Poezja - Bractwo Literackie (Gdańsk). (Gdańsk : [s.n.], 1946)
Afisz inf. o poranku 20.01.1946 r.
Keywords: Lau, Jerzy -- (1917-1970).; Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- życie intelektualne